1998
DOI: 10.1007/s100480050052
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of a commoner form of recessive amyotrophic lateral sclerosis to chromosome 15q15-q22 markers

Abstract: Autosomal recessive familial amyotrophic lateral sclerosis (RFALS) is a rare form of ALS that usually presents at an early age with slow progression of symptoms. RFALS is clinically and genetically heterogeneous and the locus of RFALS type 3 was mapped to 2q33 (ALS2) in a single family. We now report linkage of a more-common form of RFALS to chromosome 15q15-q22 markers (ALS5) and show further genetic locus heterogeneity in RFALS. ALS5 is the locus for most families with RFALS and appears to be present in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(70 citation statements)
references
References 14 publications
3
66
0
1
Order By: Relevance
“…Although human disease-causing mutations have not yet been attributed to mutations in Zfp106 (ZNF106 in humans), it is notable that the human ZNF106 locus resides within a region of chromosome 15 that is associated with both a juvenile recessive form of amyotrophic lateral sclerosis (ALS5) and axonal autosomal-recessive Charcot-Marie Tooth disease (CMT2X) (59,60). Mutations in Spatacsin (SPG11), a gene first associated with spastic paraplegia, have been associated with patients with ALS5 or CMT2X (61).…”
Section: Discussionmentioning
confidence: 99%
“…Although human disease-causing mutations have not yet been attributed to mutations in Zfp106 (ZNF106 in humans), it is notable that the human ZNF106 locus resides within a region of chromosome 15 that is associated with both a juvenile recessive form of amyotrophic lateral sclerosis (ALS5) and axonal autosomal-recessive Charcot-Marie Tooth disease (CMT2X) (59,60). Mutations in Spatacsin (SPG11), a gene first associated with spastic paraplegia, have been associated with patients with ALS5 or CMT2X (61).…”
Section: Discussionmentioning
confidence: 99%
“…Several mutations in this gene cause slowly progressive juvenile ALS. Additional genes are being identified (7)(8)(9). Animal studies suggest more gene mutations that may cause human ALS, including neurofilaments (10), dynein (11), dynamitin (12), tubulin chaperon (13,14), and vegf (15).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…The study of three consanguineous Tunisian pedigrees originally established linkage of chr15q15-q21 to an autosomal recessive form of ALS (Hentati et al 1998). A more recent study of 25 unrelated FALS families revealed 10 pedigrees with linkage to the same region and disease associated mutations in the spatacsin (SPG11) gene (Orlacchio et al 2010).…”
Section: Genetic Loci Linked To Als 361 Als5: Spatacsin (Spg11)mentioning
confidence: 99%
“…Clinically, FALS patients with linkage to this region experience a juvenile onset, slowly progressive motor neuropathy associated with both upper and lower motor neurone signs. Disease duration is typically over 10-40 years without sensory symptoms and an absence of the feature of thin corpus callosum (Hentati et al 1998;Orlacchio et al 2010). Mutations in this gene have been previously found to be the most common cause of autosomal recessive hereditary spastic paraplegia with thin corpus callosum (HSP-TCC), a condition characterised by progressive spasticity of lower limbs, mild cognitive impairment and a thin, but otherwise normally structured, corpus callosum (Abdel Aleem et al 2011).…”
Section: Genetic Loci Linked To Als 361 Als5: Spatacsin (Spg11)mentioning
confidence: 99%